Bulk chemical composition contrast from attractive forces in AFM force spectroscopy - Silbernagl, Dorothee; Ghasem Zadeh Khorasani, Media; Cano Murillo, Natalia; Elert, Anna Maria; Sturm, Heinz (Beilstein Journal of Nanotechnology, 2021)
A key application of atomic force microscopy (AFM) is the measurement of physical properties at sub-micrometer resolution. Methods such as force–distance curves (FDCs) or dynamic variants (such as intermodulation AFM (ImAFM)) are able to measure mechanical properties (such as the local stiffness, kr) of nanoscopic heterogeneous materials. For a complete structure–property correlation, these mechanical measurements are considered to lack the ability to identify the chemical structure of the materials. In this study, the measured attractive force, Fattr, acting between the AFM tip and the sample is shown to be an independent measurement for the local chemical composition and hence a complete structure–property correlation can be obtained. A proof of concept is provided by two model samples comprised of (1) epoxy/polycarbonate and (2) epoxy/boehmite. The preparation of the model samples allowed for the assignment of material phases based on AFM topography. Additional chemical characterization on the nanoscale is performed by an AFM/infrared-spectroscopy hybrid method. Mechanical properties (kr) and attractive forces (Fattr) are calculated and a structure–property correlation is obtained by a manual principle component analysis (mPCA) from a kr/Fattr diagram. A third sample comprised of (3) epoxy/polycarbonate/boehmite is measured by ImAFM. The measurement of a 2 × 2 µm cross section yields 128 × 128 force curves which are successfully evaluated by a kr/Fattr diagram and the nanoscopic heterogeneity of the sample is determined.
Keywords: AFM force spectroscopy; composites; principle component analysis; structure–property correlation; van der Waals forces

(untitled) - Butt, H.-J.; Cappella, B.; Kappl, M. (Surf. Sci. Rep., 2005)

(untitled) - Silbernagl, D.; Cappella, B. (Surf. Sci., 2009)

(untitled) - Cappella, B.; Silbernagl, D. (Thin Solid Films, 2008)

(untitled) - Munz, M.; Sturm, H.; Schulz, E.; Hinrichsen, G. (Composites, Part A, 1998)

(untitled) - Ebeling, D.; Solares, S. D. (Beilstein J. Nanotechnol., 2013)

(untitled) - RosaZeiser, A.; Weilandt, E.; Hild, S.; Marti, O. (Meas. Sci. Technol., 1997)

(untitled) - Pakzad, A.; Simonsen, J.; Yassar, R. S. (Compos. Sci. Technol., 2012)

(untitled) - Huang, H.; Dobryden, I.; Thorén, P.-A.; Ejenstam, L.; Pan, J.; Fielden, M. L.; Haviland, D. B.; Claesson, P. M. (Compos. Sci. Technol., 2017)

(untitled) - Ghasem Zadeh Khorasani, M.; Silbernagl, D.; Platz, D.; Sturm, H. (Polymers (Basel, Switz.), 2019)

(untitled) - Platz, D.; Forchheimer, D.; Tholén, E. A.; Haviland, D. B. (Beilstein J. Nanotechnol., 2013)

(untitled) - Chang, J. M.; Guan, X. Y.; Chen, Y.; Fan, H. J. (Polym. Chem., 2016)

(untitled) - Sharma, S. K.; Sudarshan, K.; Pujari, P. K. (Phys. Chem. Chem. Phys., 2016)

(untitled) - Zare, Y. (Composites, Part A, 2016)

(untitled) - Park, Y. T.; Qian, Y. Q.; Chan, C.; Suh, T.; Nejhad, M. G.; Macosko, C. W.; Stein, A. (Adv. Funct. Mater., 2015)

(untitled) - Ebeling, D.; Eslami, B.; Solares, S. D. J. (ACS Nano, 2013)

(untitled) - Ghasem Zadeh Khorasani, M.; Elert, A.-M.; Hodoroaba, V.-D.; Agudo Jácome, L.; Altmann, K.; Silbernagl, D.; Sturm, H. (Nanomaterials, 2019)

(untitled) - Topolniak, I.; Hodoroaba, V.-D.; Pfeifer, D.; Braun, U.; Sturm, H. (Materials, 2019)

(untitled) - Chung, J.; Munz, M.; Sturm, H. (Surf. Interface Anal., 2007)

(untitled) - Cano Murillo, N.; Ghasem Zadeh Khorasani, M.; Silbernagl, D.; Hahn, M. B.; Hodoroaba, V.-D.; Sturm, H. (J. Appl. Polym. Sci., 2020)

(untitled) - Krotil, H.-U.; Stifter, T.; Waschipky, H.; Weishaupt, K.; Hild, S.; Marti, O. (Surf. Interface Anal., 1999)

(untitled) - Höppener, C.; Schacher, F. H.; Deckert, V. (Small, 2020)

(untitled) - Fu, W. Y.; Zhang, W. (Small, 2017)

(untitled) - Guggisberg, M.; Bammerlin, M.; Loppacher, C.; Pfeiffer, O.; Abdurixit, A.; Barwich, V.; Bennewitz, R.; Baratoff, A.; Meyer, E.; Guntherodt, H.-J. (Phys. Rev. B, 2000)

(untitled) - Sugimoto, Y.; Pou, P.; Abe, M.; Jelinek, P.; Pérez, R.; Morita, S.; Custance, Ó. (Nature, 2007)

(untitled) - Gross, L.; Mohn, F.; Moll, N.; Liljeroth, P.; Meyer, G. (Science, 2009)

(untitled) - Frisbie, C. D.; Rozsnyai, L. F.; Noy, A.; Wrighton, M. S.; Lieber, C. M. (Science, 1994)

(untitled) - Grundmeier, G.; Stratmann, M. (Annu. Rev. Mater. Res., 2005)

(untitled) - Salerno, M.; Dante, S. (Materials, 2018)

(untitled) - Damircheli, M.; Payam, A. F.; Garcia, R. (Beilstein J. Nanotechnol., 2015)

(untitled) - Almonte, L.; Colchero, J. (Nanoscale, 2017)

(untitled) - Schmutz, J.-E.; Hölscher, H.; Ebeling, D.; Schäfer, M. M.; Anczykowski, B. (Ultramicroscopy, 2007)

(untitled) - Gady, B.; Schleef, D.; Reifenberger, R.; Rimai, D. S. (J. Adhes., 1998)

(untitled) - Das, S.; Sreeram, P. A.; Raychaudhuri, A. K. (Nanotechnology, 2007)

(untitled) - Fronczak, S. G.; Dong, J. N.; Browne, C. A.; Krenek, E. C.; Franses, E. I.; Beaudoin, S. P.; Corti, D. S. (Langmuir, 2017)

(untitled) - Fronczak, S. G.; Browne, C. A.; Krenek, E. C.; Beaudoin, S. P.; Corti, D. S. (J. Colloid Interface Sci., 2018)

(untitled) - Bhattacharya, B.; Michalchuk, A. A. L.; Silbernagl, D.; Rautenberg, M.; Schmid, T.; Feiler, T.; Reimann, K.; Ghalgaoui, A.; Sturm, H.; Paulus, B.; Emmerling, F. (Angew. Chem., Int. Ed., 2020)

(untitled) - Fankhänel, J.; Silbernagl, D.; Ghasem Zadeh Khorasani, M.; Daum, B.; Kempe, A.; Sturm, H.; Rolfes, R. (J. Nanomater., 2016)

(untitled) - Butt, H.-J.; Graf, K.; Kappl, M. (Physics and Chemistry of Interfaces, 2003)

Intermolecular and Surface Forces - Israelachvili, J. N. (Elsevier Academic Press, 2011)

Van der Waals Forces : A Handbook for Biologists, Chemists, Engineers, and Physicists - Parsegian, V. A. (Cambridge University Press, 2005)

(untitled) - Hamaker, H. C. (Physica (Amsterdam), 1937)

(untitled) - Ghasem Zadeh Khorasani, M.; Silbernagl, D.; Szymoniak, P.; Hodoroaba, V.-D.; Sturm, H. (Polymer, 2019)

(untitled) - Szymoniak, P.; Pauw, B. R.; Qu, X. T.; Schonhals, A. (Soft Matter, 2020)

(untitled) - Lam, D. C. C.; Chong, A. C. M. (Mater. Sci. Eng., A, 2000)

(untitled) - Silbernagl, D.; Schlesier, T.; Fritsche, S.; Sturm, H. (J. Open Res. Software)
to be submitted

(untitled) - Wojdyr, M. (J. Appl. Crystallogr., 2010)